Effectiveness of Toothpaste and Mouthwash Containing Ethanol Extract of Butterfly Pea Flower (Clitoria ternatea L.) in Inhibiting Streptococcus mutans: A Causative Agent of Dental Caries - Dendy Murdiyanto Mur; Sartari Entin Yuletnawati; Mutiara Aurellia Widyarini; Sabrina Belqis Putri Salami (FKG Universitas Syiah Kuala, 2026)
The high prevalence of dental caries in developing countries, including Indonesia, underpins this study. Dental caries is primarily caused by Streptococcus mutans, a bacterium responsible for tooth decay. Toothpaste and mouthwash are commonly used to maintain oral hygiene. The butterfly pea flower (Clitoria ternatea L.) contains bioactive compounds such as flavonoids, alkaloids, saponins, and tannins, which exhibit antibacterial properties and may inhibit bacterial growth. This study evaluates the antibacterial effects of toothpaste and mouthwash formulated with ethanol extract of butterfly pea flower against Streptococcus mutans. A true experimental laboratory design was applied, using a post-test-only control group model with six treatment groups. Toothpaste formulations were prepared at concentrations of 50%, 55%, 60%, and 65%, along with positive and negative control groups. Mouthwash formulations were evaluated at concentrations of 50%, 60%, 65%, and 70%, also including corresponding control groups. Each experimental group was tested in quadruplicateThe results of the study analyzed using the one-way ANOVA test showed a statistically significant difference (p < 0.05) in antibacterial efficacy among the groups. The highest inhibition was observed with the combination of 50% toothpaste and 60% mouthwash. This finding indicates that butterfly pea flower extract falls into the category of strong antibacterial agents, based on the interpretation of the agar diffusion test, which was effective in inhibiting Streptococcus mutans, the bacterium responsible for dental caries.